ARTIFICIAL INTELLIGENCE IN LANGUAGE LEARNING: SIMPLIFYING EDUCATION THROUGH TECHNOLOGY - Kalauova Sogdiana Saydullayevna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This paper discusses the growing role of artificial intelligence (AI) in helping students learn foreign languages. The purpose is to explain how AI tools make language learning more effective by offering personalized support. The study is based on an analysis of current academic research and practical examples of AI in classrooms. Results show that AI increases motivation, provides faster feedback, and saves time for teachers. These findings are important for modern education and show that AI can be used to improve learning outcomes in both schools and online environments.